[Cranfield DrivAer] CAD_Pack_6 Strakes - Francisco Soares, Renan; Knowles, Andrew; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Strakes CAD Pack (35% scaled-version), including:1. DrivAer_hp - Strakes (Lower-pair S-size):Lower pair of strakes, in nominal Small size.2. DrivAer_hp - Strakes (Lower-pair M-size):Lower pair of strakes, in nominal Medium size.3. DrivAer_hp - Strakes (Lower-pair L-size):Lower pair of strakes, in nominal Large size.4. DrivAer_hp - Strakes (Upper-pair S-size):Upper pair of strakes, in nominal Small size.5. DrivAer_hp - Strakes (Upper-pair M-size):Upper pair of strakes, in nominal Medium size.6. DrivAer_hp - Strakes (Upper-pair L-size):Upper pair of strakes, in nominal Large size.CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(Lower-set) = lower pais of strakes.(Upper-set) = upper pais of strakes.(Full-set) = both lower and upper pairs of strakes. CAD designed and uploaded by: Renan F Soares - PhD in Aerospace Applied Aerodynamics Group Cranfield University, United Kingdom
Keywords: CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Strakes'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'